2009
DOI: 10.1007/s00418-009-0616-y
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 expression in rat oral mucosa

Abstract: The oral mucosa is a highly specialised, stratified epithelium that confers protection from infection and physical, chemical and thermal stimuli. The non-keratinised junctional epithelium surrounds each tooth like a collar and is easily attacked by foreign substances from the oral sulcus. We found that TRPV2, a temperature-gated channel, is highly expressed in junctional epithelial cells, but not in oral sulcular epithelial cells or oral epithelial cells. Dual or triple immunolabelling with immunocompetent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 32 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…Recently, it was revealed that TRPV2 in macrophages is essential for phagocytosis (Link et al, 2010), as well as tumor necrosis factor-a and IL-6 production (Yamashiro et al, 2010). TRPV2 expression was also shown in monocyte-related cell types such as Langerhans cells (Shimohira et al, 2009; Link et al, 2010) and phagocytic retinal pigment epithelial cells where TRPV2 may regulate vascular endothelial growth factor-A secretion (Cordeiro et al, 2010). The precise characterization of TRPV2-expressing immune cells in rosacea has to await further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that TRPV2 in macrophages is essential for phagocytosis (Link et al, 2010), as well as tumor necrosis factor-a and IL-6 production (Yamashiro et al, 2010). TRPV2 expression was also shown in monocyte-related cell types such as Langerhans cells (Shimohira et al, 2009; Link et al, 2010) and phagocytic retinal pigment epithelial cells where TRPV2 may regulate vascular endothelial growth factor-A secretion (Cordeiro et al, 2010). The precise characterization of TRPV2-expressing immune cells in rosacea has to await further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotonicity [78,170], stretch (cell membrane stretch) [10,89] 17p11.2 TRPV4/ENSG00000111199 Hypotonicity [55,63,[171][172][173][174][175][176][177], shear (flow chamber) [61,175,178] (isolated perfused carotid artery) [65,66], stretch (silicon chamber) [179] (uniaxial cyclic stretch or static stretch) [180] (cytometric experiments) [181] (overventilation [72] or elevated hydrostatic pressure [60] in isolated murine lungs) Gong et al [54] subsequently identified that mutation of Inactive (IAV), the only other TRPV homologue in Drosophila, results in lack of NAN expression in proximal cilia, and vice versa, suggesting that both IAV and NAN may contribute to a heteromultimeric transduction channel in vivo. While these data clearly implicate a role of NAN in chordotonal mechanotransduction, it is important to note that they do not prove a direct sensory role of the channel, which may equally constitute an essential component of the early downstream signaling pathway.…”
Section: Trpv2/ensg00000154039mentioning
confidence: 99%
“…In contrast to TRPV1, TRPV2 occurs primarily in medium and large diameter afferent neurons (Zhang et al, 2004). In the rat oral mucosa, TRPV2 is not only present in subepithelial nerve fibers, but also in junctional epithelial cells surrounding each tooth, Langerhans cells, dendritic cells, macrophages and endothelial cells of venules, but not in oral epithelial cells (Shimohira et al, 2009). In the rat and guinea-pig small intestine, TRPV2 is found in nerve fibers within the muscularis and myenteric plexus as well as in myenteric cell bodies (Kashiba et al, 2004; Zhang et al, 2004).…”
Section: Expression and Functional Implications Of Trp Channels In Thmentioning
confidence: 99%